Spleen iron, molybdenum, and manganese concentrations are coregulated in hepcidin‐deficient and secondary iron overload models in mice. Issue 10 (23rd July 2019) - Cavey, Thibault; Latour, Chloé; Island, Marie-Laure; Leroyer, Patricia; Guggenbuhl, Pascal; Coppin, Hélène; Roth, Marie-Paule; Bendavid, Claude; Brissot, Pierre; Ropert, Martine; Loréal, Olivier
ABSTRACT: Iron excess increases the hepatic expression of hepcidin, the systemic iron metabolism regulator that favors iron sequestration in the spleen. Genetic iron overload related to hepcidin insufficiency decreases the spleen iron concentration and increases hepatic iron concentration, whereas during secondary iron overload, the hepcidin expression increases together with spleen iron concentration in addition to hepatic iron concentrations increase. Links between iron metabolism and other metals being suggested, our aim was to investigate, during iron overload, the relationships between the hepatic hepcidin expression level and the hepatic and splenic concentrations of iron, manganese, copper, zinc, and molybdenum, determined using inductively coupled plasma mass spectrometry. Hepcidin‐deficient mice, secondary iron overload mice models, and their respective controls were studied. Spleen molybdenum and manganese concentrations paralleled the modulation of both spleen iron concentrations, increasing in secondary iron overload and decreasing in hepcidin deficiency related iron overload, as well as hepatic hepcidin mRNA expression. Our data suggest that iron, manganese, and molybdenum metabolisms could share mechanisms controlling their distribution that are associated to hepcidin modulation. In diseases with abnormal hepcidin levels, including chronic inflammation, special attention should be paid to those metals that can participate with the phenotype.—Cavey, T., Latour, C., Island, M.‐L., Leroyer, P., Guggenbuhl, P., Coppin, H., Roth, M.‐P., Bendavid, C., Brissot, P., Ropert, M., Loréal, O. Spleen iron, molybdenum, and manganese concentrations are coregulated in hepcidin‐deficient and secondary iron overload models in mice. FASEB J. 33, 11072–11081 (2019). www.fasebj.org